Uma implementa??o em software do subsistema de transmiss?o do padr?o ISDB-TB - Paiva, Marcelo Carneiro de (2009)
The ISDB-TB system is formed by a set of subsystems with their own specifications, which define the behavior of their devices. The transmission subsystem deals with the processing performed on the bit stream before being sent through the communication channel. Although the standard specifes the blocks that compound this subsystem diagram, its description is very summarized, and can result in misinterpretation. This paper aims at providing a complete and detailed reference on the operation of ISDB-TB physical layer standard.